2021
DOI: 10.3390/vetsci8030042
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Efficacy of Fenbendazole and Pyrantel Pamoate Treatments against Intestinal Nematodes of Stud and Performance Horses

Abstract: Nematodes are an important cause of disease and loss of performance in horses. Changes in the parasitic fauna of horses have occurred in the past few decades, making cyathostomins the major parasites in adult horses, while large strongyles have become less prevalent. Parascaris spp. remains the most important parasite infecting foals and weanlings. Anthelmintic resistance is highly prevalent in cyathostomins and Parascaris spp. worldwide and it must be factored into treatment decisions. To assess anthelmintic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Similarly, cyathostomin resistance to OFZ + PYR was found in 15 (out of 18) FECRTs at 2 weeks post-treatment and this reduction in FECs of animals treated with OFZ + PYR could be due to the effectiveness of PYR as anthelmintic products containing PYR alone are not available in Australia. However, resistance to a single active anthelmintics, BZs and THPs, have been consistently reported in cyathostomins worldwide ( Traversa et al, 2012 ; Canever et al, 2013 ; Lester et al, 2013 ; Sallé et al, 2017 ; Bellaw et al, 2018 ; Morris et al, 2019 ; Butler et al, 2021 ; Zanet et al, 2021 ). In early 2000, a study reported treatment failure of MOR against strongyles in Australia on two properties ( Pook et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cyathostomin resistance to OFZ + PYR was found in 15 (out of 18) FECRTs at 2 weeks post-treatment and this reduction in FECs of animals treated with OFZ + PYR could be due to the effectiveness of PYR as anthelmintic products containing PYR alone are not available in Australia. However, resistance to a single active anthelmintics, BZs and THPs, have been consistently reported in cyathostomins worldwide ( Traversa et al, 2012 ; Canever et al, 2013 ; Lester et al, 2013 ; Sallé et al, 2017 ; Bellaw et al, 2018 ; Morris et al, 2019 ; Butler et al, 2021 ; Zanet et al, 2021 ). In early 2000, a study reported treatment failure of MOR against strongyles in Australia on two properties ( Pook et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…egg is found [ 11 , 22 , 57 ]. In contrast, for a faecal egg count reduction test (FECRT) to identify drug-resistant nematode populations, a sensitive and precise quantitative method is required, and the Mini-FLOTAC method has been repeatedly shown to perform very well in FECRT studies [ 63 65 ], including studies on horses [ 32 , 66 68 ]. Reasons to consider when choosing a test based on convenience include access to the laboratories that offer tests and acceptable turnaround times for results.…”
Section: Discussionmentioning
confidence: 99%
“…leptostomus, CY. insigne, CT. longibursatus, CT. goldi, CT. calicatus, CT. minutus) has been recognized that comprises up to 99% of the cyathostomin burden in horses [ 4 , 13 , 54 , 55 , 56 , 57 , 58 , 59 ]. While the methods used in this study cannot measure the species composition of the parasite burden of individual horses, we did observe that five species of the ‘core’ group ( CT. longibursatus, CS.…”
Section: Discussionmentioning
confidence: 99%